Multifunctional molecular modulators for perovskite solar cells with over 20% efficiency and high operational stability - Dongqin Bi (Nature Portfolio, 2018)
Engineering hybrid perovskites at the molecular level to solve the stability problem remains a challenge. Here Grätzel et al. design a multifunctional molecular modulator that interacts with the perovskite via modes elucidated by solid state NMR spectroscopy and show high efficiency and operational stability.